2006
DOI: 10.1523/jneurosci.3808-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization of Cochlear Outer Hair Cells Evokes Active Hair Bundle Motion by Two Mechanisms

Abstract: There is current debate about the origin of mechanical amplification whereby outer hair cells generate force to augment the sensitivity and frequency selectivity of the mammalian cochlea. To distinguish contributions to force production from the mechanotransducer (MET) channels and somatic motility, we have measured hair bundle motion during depolarization of individual outer hair cells in isolated rat cochleas. Depolarization evoked rapid positive bundle deflections that were reduced by perfusion with the MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 55 publications
6
62
0
Order By: Relevance
“…Moreover, cochlear amplification is most important at the cochlear base, where the apical shape changes of OHCs are the most pronounced. It has been shown that electromotility forces produced by OHCs along their cell bodies cause deflection of the stereocilia (Kennedy et al, 2006). This mechanism might provide an important route for mechanical feedback contributing to cochlear amplification.…”
Section: How Does the Ajc Reshaping Of Ohcs Assist Their Function In mentioning
confidence: 99%
“…Moreover, cochlear amplification is most important at the cochlear base, where the apical shape changes of OHCs are the most pronounced. It has been shown that electromotility forces produced by OHCs along their cell bodies cause deflection of the stereocilia (Kennedy et al, 2006). This mechanism might provide an important route for mechanical feedback contributing to cochlear amplification.…”
Section: How Does the Ajc Reshaping Of Ohcs Assist Their Function In mentioning
confidence: 99%
“…The hair bundle may also provide active force pro-duction (Kennedy et al, 2005;Chan and Hudspeth, 2005a,b), which gives some amplification in the absence of somatic motility in prestin knock-out mouse (Liberman et al, 2004). Bundle amplification and somatic motility may potentially interact (Kennedy et al, 2006); thus, it is important to determine whether there is ultrastructural evidence for connections between the bundle and the lateral wall.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfate reduces somatic electromotility [6] acting directly on prestin [10]. Replacement of intracellular chloride with sulfate, in our experiment, did not appear to influence the efficacy of the extracellular applied 9AC.…”
Section: Discussionmentioning
confidence: 38%